PERMAINAN TRADISIONAL SEBAGAI JEMBATAN ANTARA BUDAYA LOKAL DAN KONSEP MATEMATIKA PADA SISWA KELAS VI - Suhermi, Lulut (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to explore the role of traditional games rooted in the local culture of Karangsari Bojong in bridging the understanding of mathematical concepts in grade VI students of Madrasah Ibtidaiyah (MI) Asy-Sya'ban Karangsari Bojong. Adopting a case study approach, this study involved grade VI students and mathematics teachers at MI Asy-Sya'ban. Data collection was conducted through participant observation in mathematics learning sessions that integrated traditional games typical of Karangsari Bojong, semi-structured interviews with students to understand their learning experiences and perceptions of the relationship between culture and mathematics through the games, and in-depth interviews with teachers regarding implementation strategies, challenges, and benefits observed. Qualitative data analysis revealed the specific types of traditional games used, how mathematical elements were integrated into them, and students' responses to this approach. Initial findings indicate that traditional games not only preserve aspects of local culture, but are also effective in concretizing abstract mathematical concepts, increasing student engagement, and creating a more contextual and enjoyable learning atmosphere. Student perceptions indicate an increase in mathematical understanding associated with culturally familiar play experiences. Teachers also identified the potential of traditional games in improving students' motivation and understanding. This study underlines the importance of utilizing local cultural richness as a relevant and innovative pedagogical resource in mathematics education at the elementary madrasah level. The implications of this study are the need for further development of traditional game integration models in the MI curriculum and teacher training to optimize their pedagogical potential in specific local cultural contexts. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi peran permainan tradisional yang berakar dalam budaya lokal Karangsari Bojong dalam menjembatani pemahaman konsep matematika pada siswa kelas VI Madrasah Ibtidaiyah (MI) Asy-Sya'ban Karangsari Bojong. Mengadopsi pendekatan studi kasus, penelitian ini melibatkan siswa kelas VI dan guru matematika di MI Asy-Sya'ban. Pengumpulan data dilakukan melalui observasi partisipatif pada sesi pembelajaran matematika yang mengintegrasikan permainan tradisional khas Karangsari Bojong, wawancara semi-terstruktur dengan siswa untuk memahami pengalaman belajar dan persepsi mereka tentang keterkaitan budaya dan matematika melalui permainan tersebut, serta wawancara mendalam dengan guru mengenai strategi implementasi, tantangan, dan manfaat yang diamati. Analisis data kualitatif mengungkapkan jenis-jenis permainan tradisional spesifik yang digunakan, bagaimana elemen matematika terintegrasi di dalamnya, dan respons siswa terhadap pendekatan ini. Temuan awal menunjukkan bahwa permainan tradisional tidak hanya melestarikan aspek budaya lokal, tetapi juga efektif dalam mengkonkretkan konsep matematika yang abstrak, meningkatkan keterlibatan siswa, dan menciptakan suasana belajar yang lebih kontekstual dan menyenangkan. Persepsi siswa menunjukkan adanya peningkatan pemahaman matematika yang dikaitkan dengan pengalaman bermain yang familiar secara budaya. Guru juga mengidentifikasi potensi permainan tradisional dalam meningkatkan motivasi dan pemahaman siswa. Penelitian ini menggarisbawahi pentingnya memanfaatkan kekayaan budaya lokal sebagai sumber daya pedagogis yang relevan dan inovatif dalam pendidikan matematika di tingkat madrasah ibtidaiyah. Implikasi penelitian ini adalah perlunya pengembangan lebih lanjut model integrasi permainan tradisional dalam kurikulum MI dan pelatihan guru untuk mengoptimalkan potensi pedagogisnya dalam konteks budaya lokal yang spesifik.